Privasi vs data peribadi (Privacy To Personal Data Protection: Conceptual and Contextual Landscape) - Zulhuda, Sonny (2017)
The question of data privacy and how to protect it is increasingly critical in today's digital economy. There is a need to understand the concept of data privacy in the context of the digital economy where the proliferation of personal information has triggered the commodification of personal data. In this talk, those concept is being discussed in the light of the laws on personal data protection in Malaysia. This presentation is part of the programmes by the Personal Data Protection Commissioner's Office to educate Malaysian public and data users about Personal Data Protection Act 2010 nation-wide.